Exploring the association between perceived male attitudes and female attitudes toward the discontinuation of Female Genital Mutilation/Cutting in Egypt - Zsabokorszky, Zita; Van de Velde, Sarah; Michielsen, Kristien; Van Eekert, Nina (Frontiers in Sociology, 2023)
Introduction There are 200 million girls and women alive worldwide that have undergone the practice of Female Genital Mutilation/Cutting (FGM/C) and 4 million girls are at risk of undergoing the practice each year. FGM/C provides no known health benefits, while puts a plethora of medical, psychological, and sexual health risks into perspective. One of the countries where the prevalence of FGM/C is the highest in the World, even though local authorities legally banned the practice in 2008, is Egypt. Within the Egyptian context, there are several complex socioeconomic, religious, and cultural drivers that influence the familial decision making of the daughters being cut. Female attitudes hold great significance in the process, because mothers and female family members are typically the prime decision makers at the daughter's circumcision. However, whilst FGM/C is often performed to enhance marriageability and address male preferences, in practicing communities there is little to no open communication between men and women about the practice, making women rely on their perceptions on FGM/C related expectations of men. Even though the connection between female and perceived male attitudes toward the discontinuation was established almost 20 years ago, since then to our knowledge little is known about the further characteristics of this association. Therefore, this study aims to explore the association between female and perceived male attitudes within families of a younger cohort and moreover attempts to provide a more layered picture of it within different levels of education. Methods To explore the relation between female and perceived male attitudes toward the discontinuation of FGM/C we conducted a 3-step binary logistic regression model. Results Our results show that women are significantly less likely to favor a continuation of FGM/C if they think men are disapproving of the practice, compared to women that think men want it to continue. The strength of this association partially varies between the different levels of education as it is less pronounced at the level of secondary education, compared to the reference group. Discussion In alignment with previous findings in the literature, women were more likely to support the discontinuation of FGM/C if they believed that men want the practice to discontinue as well and vice versa. At a higher level of secondary education however this association is less pronounced. This result concludes that the role of perceived male attitudes should be an important factor associated with female ones and studied further, and underlines the importance of education in women empowerment.